(3eY JWHjbGJ YedjIs - (3LeGd(B, (3MhGTs ((3GdbGgQI(B:s (3GjJQGc ddWHGYI hGdfTQhGdJhRjY(B,s, 2005)
(3eaghe GdJaGhV hGdeUWdMGJ GdeTGHgI(B- (3eLGdGJ hTQhW hebheGJ GdJaGhV(B- (3TQhW GdJaGhV(B- (3ebheGJ GdJaGhV GdaYGd(B- (3GSJQGJjLjGJ hSjGSGJ hJcJjcGJ GdJaGhV(B- (3SjGSGJ GdJaGhV(B- (3efGgL hhSGFd GdEJUGd GdJaGhV(B- (3CSdhH GNJjGQ hEYOGO hJOQjH(B- (3aQjb GdJaGhV(B- (3GLQGAGJ GdJaGhV(B- (3GdJaGhV GdGefj(B- (3GdbjGSGJ GdYedjI dENJjGQ GdeaGhV(B- (3JWHjbGJ YedjI dehGba JaGVdjI(B- (3fehPL dNWI YedjI GdJaGhV (B.s
(3GdeQGLY U(B.361s
Keywords: (3EOGQI GdCReGJs; (3GdJaGhVs; (3GdeaGhVGJ(B- (3EOGQI GdCYeGds